Distinct and shared gene expression for human innate versus adaptive helper lymphoid cells. Issue 2 (4th February 2020) - Ercolano, Giuseppe; Wyss, Tania; Salomé, Bérengère; Romero, Pedro; Trabanelli, Sara; Jandus, Camilla
Abstract: Innate lymphoid cells (ILCs) are the latest identified innate immune cell family. Given their similarity in transcription factor expression and cytokine secretion profiles, ILCs have been considered as the innate phenocopy of CD4 Th cells. Here, we explored the transcriptome of circulating human ILC subsets as opposed to CD4 Th cell subsets. We describe transcriptomic differences between total ILCs and total CD4 Th cells, as well as between paired innate and adaptive cell subsets (ILC1 vs. Th1; ILC2 vs. Th2; and ILC3 vs. Th17 cells). In particular, we observed differences in expression of genes involved in cell trafficking such as CCR1, CCR6 and CXCR3, innate activation and inhibitory functions, including CD119, 2B4, TIGIT, and CTLA‐4, and neuropeptide receptors, such as VIPR2. Moreover, we report for the first time on distinct expression of long noncoding RNAs (lncRNAs) in innate vs. adaptive cells, arguing for a potential role of lncRNA in shaping human ILC biology. Altogether, our results point for unique, rather than redundant gene organization in ILCs compared to CD4 Th cells, in regard to kinetics, fine‐tuning and spatial organization of the immune response. Graphical Abstract: Human ILCs and CD4 Th cells show shared, but also distinct transcriptomic profiles, including in lncRNAs, supporting their distinct temporal and spatial activation during immune responses.